A motivational phone call improves participation to screening colonoscopy for those with a positive FIT in a national screening programme (NCT 03276091). Issue 12 (December 2018) - Gandilhon, Clémentine; Soler-Michel, Patricia; Vecchiato, Léa; Chaunier, Claude; Fay, Isabelle; Walter, Thomas; Rivory, Jérôme; Saurin, Jean-Christophe; Ponchon, Thierry; Pioche, Mathieu
Abstract: Background: A large proportion of individuals with a positive faecal immunologic test (FIT) will never undergo the recommended colonoscopy despite a full sequence of reminders. Aims: This prospective study aimed to recruit refractory individuals by a motivational personalised phone call given by a screening physician. Methods: We evaluated the impact of a motivational phone call given by a physician of the screening organisation in order to convince patients with positive FIT to undergo a colonoscopy. Results: 115 individuals with a positive FIT were targeted. After GP phone call, it was ascertained that 15 had had a colonoscopy, one died, one moved outside the region, and the GP refused the study phone call for 13. Finally, we attempted to call 85 individuals; 24 could not be reached, 5 colonoscopies had been performed, and thus 56 individuals were included. The main reason for colonoscopy refusal (33.9%) was wrong advice from the GP or the gastroenterologist. Among those included, 33.9% (19/56) underwent the colonoscopy within 22.7 months after FIT; 1 invasive cancer, 18 adenomas and 9 serrated sessile lesions were found. Conclusion: Motivational phone call performed by a physician from the screening organisation is effective to recruit a third of refractory individuals. Education for GPs and gastroenterologists is necessary to increase participation to colonoscopy and to avoid the performance of an inappropriate secondary FIT. Trial Registration: NCT 03276091.